GAMBARAN FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KERACUNAN PETUGAS PEST CONTROL DI DENPASAR - Agnes Ayu Biomi (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
Pest control officers have a fairly high level of risk in their work so they require the use of complete PPE, especially when exposed to pesticides for a long time and frequency. Pesticides can enter through the skin, into the mouth or through inhalation. Therefore, this study aims to determine the factors related to the characteristics of pest control officers including age, education level, knowledge of K3, nutritional status, frequency of spraying, number of types of pesticides and their relationship with the level of poisoning in the blood of pest control officers. This study used a cross sectional method with a sample of 25 people. Sampling was carried out using the total sampling method to obtain an overview of the factors associated with the level of poisoning by pest control officers in Denpasar. Based on the research conducted, the results obtained that there is a description of the factors associated with the level of pesticide poisoning. The results of the examination of cholinesterase activity in the blood can be used as confirmation (confirmation) of the occurrence of pesticide poisoning in a person. The process of pesticide poisoning is caused by the interaction between chemical agents or chemical agents, humans as hosts and supporting environmental factors. Chemical agents resulting from human activities can have various effects on health. The level of K3 knowledge and the use of personal protective equipment is very important for pest control officers because it has an impact on long-term health and exposure to pesticides that can cause poisoning.   Keywords         : Overview, Factors, Poisoning, Pesticides, Officer